De l’autonomie au système d’autorité la favorisant - Laurent Van Belleghem; Jean-Christophe Michel; Inès Haeffner (Activités)
Repeated calls for greater autonomy at work are becoming ever louder, yet in concrete terms these calls do not always say what (or whom) autonomy is supposed to serve. Taking the results of a participatory intervention that led to a profound transformation in the organization of a social housing agency, this article attempts to provide answers to these questions. It takes as its starting point the notion of authority, which is presented not through its classical meaning (attached to the legitimate power someone exercises over others) but through the object that a group of actors is able to identify as “authoritative” within their common activity, guiding it. We hypothesize that economy of service has contributed to shifting this “common object of work” towards a service relationship issue that the guidelines produced by the organization can never fully predict. The majority of business organizations have however mostly remained attached to a structure inherited from industry and aimed at strict compliance with prescribed rules. From then on, a gap has been established between the system of formal authority and the “common object of work” supposed to be authoritative for the actors of the system. Supporting companies in their organizational transformation therefore means knowing how to “re-adjust” the system of authority to “what is now authoritative”. In the social housing agency, the emergence of an organizational model “built by semi-autonomous teams” to better respond to the issue of providing a service to tenants can be interpreted as a response to this adjustment issue. That autonomy is called upon on this occasion is surely no coincidence. However, it does not appear here to be the response to a desire for individual autonomy or as an end in itself (as managerial literature often suggests) but rather as collective autonomy on the one hand, as a means of greater cooperation on the other, with the aim of promoting the relevance of the always unique responses to be provided to the beneficiaries. This “use” of autonomy makes it possible to better understand, in this case, for what and for whom it is used. In concrete terms.